Single Atrium and Miscarriages - Kojqiqi, Fatos; Kojqiqi, Arben; Jusufi, Ismet; Kojcici, Besnik (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Background A single atrium is a very rare heart condition, in which the inter atrial septum is missing. These congenital heart defects usually are surgically corrected after birth.Case Presentation We present a successful surgical repair of a single atrium (SA) in a 27-year-old woman, who has a complete missing of the atrial septum, without coexisting valvular pathology. The SA diameter was 9.97 × 6.18 cm and the Systemic blood flow/pulmonary blood flow (Qp/Qs) was 4.1 due to the single atrium. Surgical correction consisted of creating a new atrial septum, using a double-velor patch. At first- and second-year follow up, the patient was in a very good condition and without any symptoms present. We consider that the diagnoses of single atrium, especially in child bearing women, should be done in appropriate time, to avoid miscarriages, preterm births and other complications associated.Conclusion There are many case reports that show good surgical repair of single atrium and without late complications. In our case, we have obtained a very good surgical repair, without AV bundle damage and no residual shunt demonstrated on intraoperative transesophageal echocardiography.
Keywords: single atrium; common atrium; miscarriages; preterm births; heart defect; pregnancy